DEVELOPING ENGLISH LITERACY-BASED ACTIVITIES FOR ELEMENTARY STUDENTS - P.R. Arditami; N.L.P. Artini; L.G.R. Budiarta (Universitas Pendidikan Ganesha, 2019)
Problems related to elementary students’ English literacy in Indonesia remain the biggest challenge to be solved. Lack of learning sources in English language, lack of English lesson period given to the students, monotonous learning activities as well as teacher’s incompetence in teaching English to the students affect students’ English literacy. Considering the mentioned problems, this current research aimed at developing English literacy-based activities for the first semester of 5th grade elementary students. The study applied Design and Development (D&D) model. There were two kinds of data; qualitative data and quantitative data. Qualitative data were gathered through observation and document study. Meanwhile, quantitative data were gathered through experts judgement and literacy test. The result of this research was a product in the form of students’ worksheet developed through four phases such as analysis, design, development, and evaluation. The students’ worksheet consisted of six topics such as self identity, daily activities, school environment, family, and house. Each topic consisted of various English literacy-based activities such as singing song, playing game, doing survey, doing interview, role play, drawing house plan and classroom plan, making schedule. The developed product was examined to find its effectiveness by trying it out to the 5th grade elementary students. It was proven that the product is effective in enhancing students’ English literacy skill, proven from the result of paired t-test Sig. (2.tailed) (0.00 < 0.05).